Validation of a Smartphone Application for Assessment of Risk of Venous Thromboembolism in Obstetrics and Gynecology - Galila F. Zaher; Soheir S. Adam (Journal of King Abdulaziz University: Medical Sciences, 2023)
Venous thromboembolism is a serious but potentially preventable condition. However, morbidity and mortality occur due to lack of thrombo-prophylaxis. Obstetrics and gynecology patients are at risk for developing venous thromboembolism. To improve adherence to thromboprophylaxis in this patient population, we developed a smart phone clinical decision support system designed to assess risk score and recommend thromboprophylaxis. Clinical data were collected by review of electronic medical charts. The risk score and thromboprophylaxis recommendations were calculated for each patient by clinical decision support system and by an expert hematologist and results were compared for correlation. We hypothesize that the system is a valid tool for risk assessment in obstetrics and gynecology patients. A total of 188 female patients admitted at King Abdulaziz University Hospital between December 2015 and March 2016 were included. One hundred and sixteen were gynecology, and 72 were obstetric patients with a mean age of 40.7 (± 12.8). The risk score obtained by the system showed a strong correlation with that of the expert hematologist’s opinion (r = 83%). The clinical decision support system showed a good correlation for thromboprophylaxis decision as well. Accessibility and ease of use of clinical decision support system can improve the clinical outcome of hospitalized patients.